An exploration of displacement and alienation in post-colonial context: a close study of V.S. Naipaul’s The Mimic Men and Samuel Selvon’s The Lonely Londoners - Akter, Shammy (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.